The ultrastructure of the muscle coat of human gastro-oesophageal junction, with special reference to “interstitial cells of Cajal”† - Maria-Simonetta, Faussone-Pellegrini; Romagnoli, Paolo; Cortesini, Camillo (Frontiers in Neuroscience, 2013)
The muscle coat of the human lower oesophageal sphincter and stomach was studied 5 cm above and 4 cm below the gastro-oesophageal junction. Four subjects were operated on for motility disorders of the oesophagus, two for a hypertensive lower oesophageal sphincter and two for an epiphrenic diverticulum; six subjects were operated on for oesophageal or gastric carcinomas. Specimens were ﬁxed in phosphate-buffered OsO4, embedded in Epon, contrasted with uranyl acetate and lead citrate and observed under a Siemens Elmiskop Ia electron microscope. Both the oesophageal and gastric muscle cells, which showed features typical of this cell type, were innervated by multiple varicosities that were rich in synaptic vesicles; these varicosities were generally rarely encountered at distances less than 1000 Å from muscle cells. Only a very few, close neuromuscular junctions were detected. Special cells, which correspond to the “interstitial cells of Cajal” as reported by other authors, were discerned at the periphery of muscle cell bundles. These cells were characterized by an elongated cell body with many thin branches and an oval, sometimes indented nucleus. Some pinocytotic vesicles were located at the cell periphery. These cells were surrounded by a discontinuous basal lamina and were seen in close contact with each other and with muscle cells; the close contact areas were often very wide. The cytoplasm contained variable amounts of mitochondria, a well-developed smooth endoplasmic reticulum and a Golgi complex. As a characteristic feature, bundles of thin ﬁlaments were located at the cell periphery and were attached to electron-dense areas of the cell membrane. Morphologically, these ﬁlaments resembled myofilaments; they were present in variable amounts and were sometimes very numerous. The observation that the cytoplasmic organelles and ﬁlaments varied in number, is probably related to the different functional properties of these cells. Interstitial cells were richly innerva